An Assessment of the Plant and Mycorrhizal Community at Steeves Lake Shoreline, Colomac Mine, NWT - Hamp, Rebekah; Stevens, Dr. Kevin (Scholars Commons @ Laurier, 2018)
This study focused on the environmental impacts of mining and potential techniques to mitigate them. The goals of this study were to (1) Quantify vegetation and fungal colonization at a remediated mine site in northern Canada, and to determine if there were effects from petroleum hydrocarbon contamination, (2) Determine the response of northern plants inoculated with mycorrhizal fungi to diesel contamination. Mycorrhizal colonization was observed in field collected roots and trends in colonization and vegetation cover suggested that these communities were no longer impacted by residual contamination. Mean hyphal colonization of Elymus trachycaulus roots collected over two years was 47.3±3.8% and 49.3±2.7% respectively, and Festuca ovina and Hordeum jubatum collected during one year had mean hyphal colonization of 64.1±2.1% and 56.6. ±2.7% respectively. Two mycorrhizal plants (E. trachycaulus and Erigeron acris) and one non-mycorrhizal plant (Carex aquatilis) were grown with or without mycorrhizal fungi and exposed to four levels of diesel contamination (3,460, 6,500, 10,000 mg/kg and a control). Responses varied between species, though results suggest that PHC concentrations ≥ 6,500 mg/kg significantly affected growth. Mean shoot/root ratio of C. aquatilis plants decreased from 0.15 ± 0.01 in the control treatment to 0.10 ± 0.01 and 0.09 ± 0.01in the treatments receiving 6,500 and 10,000 mg/kg diesel respectively. Growth responses between plant species with and without mycorrhizal inoculum suggest that an association with AMF influenced plant growth responses. Significant differences in shoot biomass between inoculum treatments were observed in the mycorrhizal plant species though not in the non-mycorrhizal species. Mean shoot fresh weight of E. trachycaulus was significantly higher in plants inoculated with mycorrhizal fungi (0.12 g ± 0.01) compared to non-inoculated plants (0.09 g ± 0.0). Mean shoot fresh weight of E. acris plants was 0.10 g ± 0.01 in plants inoculated with mycorrhizal fungi, significantly ...